QT dispersion in athletic left ventricular hypertrophy - Mayet, J.; Kanagaratnam, P.; Shahi, M.; Senior, R.; Doherty, M.; Poulter, N. R.; Sever, P. S.; Handler, C. E.; Thom, S. A.; Foale, R. A. (American Heart Journal, 1999)
OBJECTIVE: To assess whether physiologic left ventricular hypertrophy as a result of physical training is associated with an increased QT length or dispersion. METHODS: Thirty-three subjects were assessed. These consisted of a group of international endurance athletes (including 8 rowers, 2 cyclists, and 1 triathlete), a group of 12 professional soccer players, and a further group of 10 control subjects. Each underwent 2-dimensional echocardiography and 12-lead electrocardiographic examination. RESULTS: Left ventricular mass index was considerably greater in both the endurance athlete (163.3 +/- 14.4 g/m2; P <.01) and soccer player groups (144.2 +/- 5.5 g/m 2; P <.05) compared with the controls (109.2 +/- 6.3 g/m2). In spite of these large differences in cardiac structure there were no significant differences in QT parameters between the groups (QT dispersion 56.9 +/- 5.5, 68.5 +/- 9.5, and 67.2 +/- 12.6 ms; QTc dispersion 61.4 +/- 9.2, 69.4 +/- 13.3, and 54.2 +/- 6.5 ms; maximum QT 402 +/- 10.3, 404 +/- 9.6, and 392 +/- 14.0 ms; and maximum QTc 404 +/- 7.0, 413 +/- 9.3, and 399 +/- 9.9 ms among endurance athletes, soccer players, and controls, respectively). CONCLUSION: Left ventricular hypertrophy occurring as a consequence of athletic training does not appear to be associated with a major increase in QT length or QT dispersion.